Kajian Risiko Pajanan Sinar Gama dan Radon pada Pekerja di Area Terowongan Eksplorasi Uranium Remaja, Kalimantan Barat - Noor, Tajudin; Tejamaya, Mila; Saputra, Miki Arian; Purwanti, Tri (EKSPLORIUM, 2020)
A risk assessment of gamma radiation and radon gas exposure is carried out in the uranium exploration tunnel area to protect workers from the ionizing radiation hazards in the workplace. Measurement of gamma-ray exposure and radon gas concentrations were carried out in Remaja uranium exploration tunnel and around the workers camp in Kalan Area, West Kalimantan. Gamma exposure was measured using a gamma survey meter while radon (222Rn/220Rn) using RADUET passive detector. The concentrations of radon and thoron gas inside the tunnel generally are high, ranging from 188.84 to 495.86 Bq/m3 (375.80 Bq/m3 average) and 58.07 to 340.73 Bq/m3 (189.80 Bq/m3 average) respectively. These values are above the radon reference level (300 Bq/m3)which is recommended by the International Commission on Radiation Protection (ICRP). The annual gamma effective dose reaches 147.88mSv inside the tunnel. This value is exceeding the 20 mSv dose limit value for workers. It is necessary to control the exposure by fulfilled the principle of “as low as reasonably achievable” (ALARA) and external radiation protection to secure workers inside the tunnel from a health issue caused by gamma-ray, radon, and thoron exposures.